FAKTOR POSITIVE DEVIANCE KARAKTERISTIK KELUARGA MISKIN DENGAN STATUS GIZI ANAK USIA 0-24 BULAN DI WILAYAH KERJA PUSKESMAS MEDAN AMPLAS TAHUN 2019 - FITRIANI, EVI - (Jurnal Kesehatan Ilmiah Indonesia (Indonesian Health Scientific Journal), 2020)
The critical condition of the growth and development of a child aged 0 – 24 months is called a “critical period” because in this age the child undergoes very fast physical growth and brain development so that he needs good nutrition. Positive deviance is used to explain some factors which influence the growth and good nutrition status of children who live in poor families and in poor environment, where most of them undergo abnormal growth and development with malnutrition condition. The objective of the research was to analyze factors influence the nutrition status of child aged 0 – 24 months by positive deviance in quantitative study with complement qualitative with a survey by cross sectional approach, to collect data of characteristic of family, characteristic of child and the behavior of parent in care the child and its influence to the nutrition status with positive deviance review and to study efforts of parent in order to increase the nutrition status of child aged 0 – 24 months in Amplas Puskesmas. The number of sample in this research for qualitative study is 100 respondents taken by proportional sampling method from 10 villages. The data were analyzed by using bivariate statistic analysis with Chi-square test in confidential level of 95% and multivariate analysis with logistic regression test with OR (CI 95%), and 5 mothers as informant for qualitative data. The result of research showed that based on mother characteristic, child characteristic and mother’s behavior in taking care of child it was found from the results of statistic test that variables of education, occupation, birth weight, knowledge, attitude and interaction of mother and child have influence to the nutrition status of child aged 0 – 24 months from the poor family in AmplasPuskesmas, Districts Medan Amplas 2019 in which the dominant variable is a knowledge of mother with Exp (B) or Odd Ratio (OR) is 11.254 in Confidence Interval 95% in rage of 1.365 up to 52.754. It is recommended to the local health office and Puskesmas to support the society/mothers in pay attention to the nutrition of the child and to increase the role of local posyandu to provide socialization, extension and counseling about the nutrition status of child that related to the nutrition status of child and to increase the knowledge of mother about health issue and how to care the child in order to increase the behavior and attitude of mother in maintain the nutrition status of child not based on education and occupation of the mother.